The Role of Self-Regulated Learning in Strengthening Students' Independent Learning Character: Literature Review - Astuti, Amelia Dwi; Rozikin, Achmad Zainul (English Language in Focus (ELIF), 2024)
This study investigates the role of self-regulated learning (SRL) in developing independent learning habits among students. SRL enables people to effectively manage their learning processes by combining metacognitive skills, motivation, and behavioral strategies to achieve academic success. SRL improves students' overall quality of life by establishing structured learning habits and routines, in addition to academic performance. The findings, which were obtained through a literature review using the Sinta and Google Scholar databases, show that increased self-reliance and self-awareness throughout the stages of SRL positively contribute to personal growth and the development of desirable personality traits. Overall, the study emphasizes the importance of SRL in developing effective and autonomous learners.